Catalyst for reduction of decabromodiphenyl, preparation method and application
By using copper/indium zinc sulfide photocatalysts, light is used to promote the reduction and dehalogenation of dechlorobiphenyl, the problem of difficulty in removing dechlorobiphenyl in the prior art is solved, and efficient and environmentally friendly pollutant removal effect is achieved.
Patent Information
- Application Number
- CN202510078097.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art is difficult to effectively remove dechlorobiphenyl, a class of persistent pollutants that are extremely difficult to decompose and pose a threat to the environment and health.
A copper/indium sulfide photocatalyst is used, which consists of spherical indium sulfide as a support and copper nanoclusters as a support, and promotes the reduction and dehalogenation of dechlorobiphenyls by light irradiation.
The efficient removal of decachlorobiphenyl was achieved. The removal rate of decachlorobiphenyl reached 100% after 90 minutes of light, and the reduction rate was 0.067 min-1, which significantly reduced the harm of decachlorobiphenyl to the environment.
Smart Images

Figure CN119857501A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysts, and in particular relates to a catalyst for reducing decachlorobiphenyl, a preparation method and an application thereof. Background Art
[0002] Decachlorobiphenyl is a type of persistent pollutant that enters the atmosphere, water bodies and soil through volatilization, leakage and other pathways during use. They are extremely insoluble in water but easily soluble in fat and organic solvents, and are extremely difficult to decompose. Therefore, they can be enriched in the fat of organisms in large quantities, causing "three hazards" namely carcinogenicity, mutagenicity and teratogenicity. In this context, researchers have developed a variety of methods to remove decachlorobiphenyl. Photocatalytic reduction is a green and efficient method for treating halogenated organic pollutants. It can reduce and dehalogenate a variety of halogenated organic compounds and has received widespread attention.
[0003] Therefore, in view of the above technical problems, it is necessary to provide a catalyst for the reduction of decachlorobiphenyl.
[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0005] The purpose of the present invention is to provide a catalyst for reducing decachlorobiphenyl, a preparation method and application thereof.
[0006] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:
[0007] Catalysts for the reduction of decachlorobiphenyl include
[0008] Flower-ball-shaped indium zinc sulfide as a carrier;
[0009] And copper nanoclusters loaded on a carrier, whose loading mass is 0.01-0.25% of the mass of indium zinc sulfide. Preferably, the reduction of decachlorobiphenyl is achieved in a decachlorobiphenyl solution. More preferably, the reduction of decachlorobiphenyl can be specifically, adding a copper / indium zinc sulfide photocatalyst to a decachlorobiphenyl solution and irradiating it under a nitrogen protective atmosphere. During the illumination process, the photocatalyst can catalyze the conversion of the C-Cl bond of decachlorobiphenyl into a CH bond, thereby reducing the harm of decachlorobiphenyl to the environment. More preferably, the solvent of the decachlorobiphenyl solution can be a common solvent such as methanol, isopropanol, acetonitrile and N,N-dimethylformamide.
[0010] In one or more embodiments of the present invention, the size of the copper nanoclusters is 0.5-2 nanometers.
[0011] In one or more embodiments of the present invention, the carrier is a flower-ball-shaped indium zinc sulfide composed of nanosheets, the surface of the flower-ball-shaped indium zinc sulfide is rough, and there are gaps between the nanosheets.
[0012] In one or more embodiments of the present invention, the flower ball-shaped indium zinc sulfide is prepared by the following method:
[0013] The zinc salt, the indium salt and the sulfur source are dispersed in a mixed solvent including water and a dispersant, and a solvent thermal reaction is carried out under heating to obtain a reaction product. The product is centrifuged, washed and separated to obtain a flower ball-shaped indium zinc sulfide carrier.
[0014] In one or more embodiments of the present invention, the copper nanocluster loading is prepared by the following method:
[0015] The indium zinc sulfide carrier is dispersed in deionized water to form a suspension, and then copper salt is added. After uniform dispersion, an inert gas is introduced to remove oxygen, and the product is heated, centrifuged, washed, and dried. Preferably, the dispersion amount of the carrier in the suspension is 200 mg; the concentration is 1.33 mg / mL.
[0016] In one or more embodiments of the present invention, the volume ratio of water to dispersant is 1:(0.1-10).
[0017] In one or more embodiments of the present invention, the temperature of the thermal reaction is 160-200°C.
[0018] In one or more embodiments of the present invention, the heating temperature is 60-100°C.
[0019] In one or more embodiments of the present invention, the dispersant is selected from ethanol and glycerol.
[0020] The specific preparation method of the copper / indium zinc sulfide photocatalyst can be divided into two steps: (1) dispersing zinc salt, indium salt and sulfur source in a mixed solvent of water and dispersant in a volume ratio of 1:1, performing a solvent thermal reaction under heating for 12 hours, centrifuging, washing and separating the product to obtain a flower ball-shaped indium zinc sulfide carrier; (2) dispersing indium zinc sulfide in deionized water to form a suspension, adding copper salt, passing nitrogen to remove oxygen after uniform dispersion, heating for a certain period of time, centrifuging, washing and drying the product to obtain a copper / indium zinc sulfide photocatalyst.
[0021] Preferably, in step (1), the molar ratio of the zinc salt, the indium salt and the sulfur source is 1:2:(4-8), and the zinc salt, the indium salt and the sulfur source react fully to form indium zinc sulfide.
[0022] Preferably, the zinc salt in step (1) is zinc sulfate heptahydrate, zinc chloride, or hydrated zinc nitrate.
[0023] Preferably, the indium salt in step (1) is indium chloride tetrahydrate.
[0024] Preferably, the sulfur source in step (1) is thioacetamide.
[0025] Preferably, the temperature of the oil bath or oven heated in step (1) is 160-200° C., and the raw materials react fully to form flower-shaped indium zinc sulfide.
[0026] Preferably, in step (1), the mass ratio of copper salt to indium zinc sulfide is 0.03-0.67% to ensure that uniformly dispersed copper nanoclusters are formed on the surface of indium zinc sulfide.
[0027] Preferably, the heating temperature in step (2) is 60-100°C, preferably 70-80°C.
[0028] Further preferably, the heating time in step (2) is 1-8 hours, preferably 3-6 hours, to ensure the size and dispersion of the copper nanoclusters formed on the surface of indium zinc sulfide. Preferably, the copper nanoclusters have a size of 0.5-2 nanometers and are evenly dispersed.
[0029] Invention principle: The copper / indium zinc sulfide photocatalyst is a copper nanocluster formed on the surface of flower-shaped indium zinc sulfide, which can promote the separation and transmission of photogenerated carriers of indium zinc sulfide and enhance the affinity with decachlorobiphenyl. Photogenerated electrons can be transmitted by copper nanoclusters to reduce and dechlorinate decachlorobiphenyl into nonachlorobiphenyl and octachlorobiphenyl.
[0030] Compared with the prior art, the catalyst for decachlorobiphenyl reduction of the present invention has the following beneficial effects: the copper / indium zinc sulfide of the present invention has a large specific surface area and abundant catalytic active sites, which effectively promotes the separation of photogenerated electrons and holes, enhances the photocatalytic performance of the single indium zinc sulfide photocatalyst, and has excellent photocatalytic reduction effect on decachlorobiphenyl. After 90 minutes of illumination, the removal rate of decachlorobiphenyl is 100%, and the reduction rate is 0.067min -1 The present invention uses copper salt as raw material, and in a nitrogen atmosphere, copper nanoclusters are grown in situ on the surface of flower-shaped indium zinc sulfide by water bath heating, which promotes the photogenerated electron transfer of indium zinc sulfide, combines the affinity of copper nanoclusters with decachlorobiphenyl and the influence of solvent on the electronic reduction of photocatalyst, and enhances the effect of photocatalytic reduction of decachlorobiphenyl. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1It is the X-ray crystal diffraction pattern of indium zinc sulfide (ZnIn2S4) prepared in comparative example 1 and copper / indium zinc sulfide (0.1% Cu / ZnIn2S4) prepared in example 2.
[0033] Figure 2 It is a scanning electron microscope image of the ZnIn2S4 prepared in Comparative Example 1 and the 0.1% Cu / ZnIn2S4 photocatalyst prepared in Example 2.
[0034] Figure 3 This is a transmission electron microscope image of the 0.1% Cu / ZnIn2S4 photocatalyst prepared in Example 2.
[0035] Figure 4 It is the fluorescence emission spectra of ZnIn2S4 prepared in Comparative Example 1 and 0.1% Cu / ZnIn2S4 photocatalyst prepared in Example 2.
[0036] Figure 5 This is a photocatalytic degradation curve of decachlorobiphenyl by 0.05% Cu / ZnIn2S4, 0.1% Cu / ZnIn2S4, 0.15% Cu / ZnIn2S4, 0.2% Cu / ZnIn2S4, 0.25% Cu / ZnIn2S4 and ZnIn2S4 and 2% Cu / ZnIn2S4 photocatalysts prepared in Example 1, Example 2, Example 3, Example 4, Example 5 and Comparative Example 1 and Comparative Example 2.
[0037] Figure 6 It is a degradation curve diagram obtained by removing decachlorobiphenyl according to the implementation steps in Example 2 and Comparative Examples 3 and 4.
[0038] Figure 7 It is a degradation curve diagram obtained by removing decachlorobiphenyl according to the implementation steps in Example 2 and Comparative Examples 5, 6, 7 and 8.
[0039] Figure 8 It is a degradation curve diagram obtained by removing decachlorobiphenyl through the implementation steps in Example 2 and Comparative Example 9. DETAILED DESCRIPTION
[0040] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0041] Example 1 (0.05% / ZnIn2S4)
[0042] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0043] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 0.13:100), and transfer to a three-necked flask after complete dissolution. Pass nitrogen for 25 minutes to exclude air. Heat in a 70°C water bath for 4 hours, wash the resulting precipitate with deionized water and anhydrous ethanol by centrifugation several times, and dry under vacuum conditions at 60°C for 12 hours to obtain 0.05% Cu / ZnIn2S4 photocatalyst powder.
[0044] The samples of this embodiment were tested and found to have copper nanoclusters of about 0.5 nanometers deposited on the catalyst powder. The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction vessel. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain specific temperature; the above-synthesized 0.05% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, the solvent (N,N-dimethylformamide), etc. were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was carried out every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, and the supernatant was detected by a gas chromatograph (Agilent GC8860).
[0045] Example 2 (0.1% Cu / ZnIn2S4)
[0046] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0047] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 0.27:100), and transfer to a three-necked flask after complete dissolution. Pass nitrogen for 25 minutes to exclude air. Heat in a 70°C water bath for 4 hours, wash the resulting precipitate several times with deionized water and anhydrous ethanol by centrifugation, and dry at 60°C under vacuum for 12 hours to obtain 0.1% Cu / ZnIn2S4 photocatalyst powder.
[0048] The samples of this embodiment were tested and found to have deposited copper nanoclusters of about 0.8 nanometers on the catalyst powder. The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction vessel. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain specific temperature; the above-synthesized 0.1% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, the solvent (N,N-dimethylformamide), etc. were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was carried out every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, and the supernatant was detected by a gas chromatograph (Agilent GC8860).
[0049] Example 3 (0.15% / ZnIn2S4)
[0050] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0051] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 0.40:100). After complete dissolution, transfer to a three-necked flask. Pass nitrogen for 25 minutes to exclude air. Heat in a 70°C water bath for 4 hours, wash the resulting precipitate with deionized water and anhydrous ethanol by centrifugation several times, and dry under vacuum conditions at 60°C for 12 hours to obtain 0.15% Cu / ZnIn2S4 photocatalyst powder.
[0052] The samples of this embodiment were tested and found to have copper nanoclusters of about 1 nanometer deposited on the catalyst powder. The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction vessel. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain specific temperature; the above-synthesized 0.15% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, and the solvent (N,N-dimethylformamide) were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was performed every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, which was tested using a gas chromatograph (Agilent GC8860).
[0053] Example 4 (0.2% / ZnIn2S4)
[0054] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0055] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 0.54:100), and transfer to a three-necked flask after complete dissolution. Pass nitrogen for 25 minutes to exclude air. Heat in a 70°C water bath for 4 hours, wash the resulting precipitate with deionized water and anhydrous ethanol by centrifugation several times, and dry under vacuum conditions at 60°C for 12 hours to obtain 0.2% Cu / ZnIn2S4 photocatalyst powder.
[0056] The samples of this embodiment were tested and found to have deposited copper nanoclusters of about 1.5 nanometers on the catalyst powder. The photocatalytic degradation of decachlorobiphenyl was conducted in a glass-enclosed heat-resistant reaction vessel. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technique was used to keep the reaction system at a certain temperature; the above-synthesized 0.2% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, and the solvent (N,N-dimethylformamide) were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was performed every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, which was then tested using a gas chromatograph (GC8860 from Agilent).
[0057] Example 5 (0.25% / ZnIn2S4)
[0058] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0059] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 0.67:100), and transfer to a three-necked flask after complete dissolution. Pass nitrogen for 25 minutes to exclude air. Heat in a 70°C water bath for 4 hours, wash the resulting precipitate with deionized water and anhydrous ethanol by centrifugation several times, and dry under vacuum conditions at 60°C for 12 hours to obtain 0.25% Cu / ZnIn2S4 photocatalyst powder.
[0060] The samples of this embodiment were tested and found to have copper nanoclusters of about 2 nanometers deposited on the catalyst powder. The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction vessel. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain specific temperature; the above-synthesized 0.25% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, the solvent (N,N-dimethylformamide), etc. were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was carried out every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, and the supernatant was detected by a gas chromatograph (Agilent GC8860).
[0061] Example 6 (0.1% Cu / ZnIn2S4, deposited at 60°C)
[0062] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0063] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 0.27:100), and transfer to a three-necked flask after complete dissolution. Pass nitrogen for 25 minutes to exclude air. Heat in a 60°C water bath for 6 hours, wash the resulting precipitate with deionized water and anhydrous ethanol by centrifugation several times, and dry under vacuum conditions at 60°C for 12 hours to obtain 0.1% Cu / ZnIn2S4 photocatalyst powder.
[0064] The samples of this embodiment were tested and found to have deposited copper nanoclusters of about 0.8 nanometers on the catalyst powder. The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction vessel. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain specific temperature; the above-synthesized 0.1% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, the solvent (N,N-dimethylformamide), etc. were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was carried out every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, and the supernatant was detected by a gas chromatograph (Agilent GC8860).
[0065] Example 7 (0.1% Cu / ZnIn2S4, deposited at 90°C)
[0066] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0067] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 0.27:100), and transfer to a three-necked flask after complete dissolution. Pass nitrogen for 25 minutes to exclude air. Heat in a 90°C water bath for 3 hours, wash the resulting precipitate with deionized water and anhydrous ethanol by centrifugation several times, and dry under vacuum conditions at 60°C for 12 hours to obtain 0.1% Cu / ZnIn2S4 photocatalyst powder.
[0068] The samples of this embodiment were tested and found to have deposited copper nanoclusters of about 0.8 nanometers on the catalyst powder. The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction vessel. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain specific temperature; the above-synthesized 0.1% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, the solvent (N,N-dimethylformamide), etc. were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was carried out every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, and the supernatant was detected by a gas chromatograph (Agilent GC8860).
[0069] Example 8 (160°C hydrothermal reaction)
[0070] The difference between this embodiment and embodiment 6 is that 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate are dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide is added and stirred for 30 minutes. The above solution is transferred to a 50 ml autoclave, heat-treated in an oven at 160° C. for 12 hours, and then cooled to room temperature; the obtained precipitate is washed with deionized water and anhydrous ethanol for multiple times, and dried at 60° C. under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0071] The sample of this embodiment was tested and found that the catalyst powder deposited copper nanoclusters of about 1 nanometer. The photocatalytic reduction effect of decachlorobiphenyl was poor under the same conditions, and only 58% of decachlorobiphenyl could be converted after 90 minutes of illumination.
[0072] Example 9 (200°C hydrothermal reaction)
[0073] The difference between this embodiment and embodiment 6 is that 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate are dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide is added and stirred for 30 minutes. The above solution is transferred to a 50 ml autoclave, heat-treated in an oven at 200° C. for 12 hours, and then cooled to room temperature; the obtained precipitate is washed with deionized water and anhydrous ethanol for multiple times, and dried at 60° C. under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0074] The sample of this embodiment was tested and found that the catalyst powder deposited copper nanoclusters of about 1 nanometer. The photocatalytic reduction effect of decachlorobiphenyl was poor under the same conditions, and only 45% of decachlorobiphenyl could be converted after 90 minutes of illumination.
[0075] Comparative Example 1 (pure indium zinc sulfide, copper loading is 0):
[0076] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0077] The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction container. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain temperature; the synthesized indium zinc sulfide, the target pollutant decachlorobiphenyl, and the solvent (N,N-dimethylformamide) were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was performed every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, which was detected by a gas chromatograph (Agilent GC8860).
[0078] Comparative Example 2 (Copper loading is 2%)
[0079] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0080] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 5.4:100). After complete dissolution, transfer to a three-necked flask. Pass nitrogen for 25 minutes to exclude air. Heat in a 70°C water bath for 4 hours, wash the resulting precipitate several times with deionized water and anhydrous ethanol by centrifugation, and dry at 60°C under vacuum for 12 hours to obtain 2% Cu / ZnIn2S4 photocatalyst powder.
[0081] The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction container. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain temperature; the above-synthesized 2% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, and the solvent (N,N-dimethylformamide) were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was performed every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, which was detected by a gas chromatograph (Agilent GC8860).
[0082] Comparative Example 3 (without adding photocatalyst)
[0083] The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction container. A 300-watt xenon lamp was used as the visible light source; reflux temperature control technology was used to keep the reaction system at a certain temperature; the target pollutant decachlorobiphenyl and solvent (N,N-dimethylformamide) were added to the reactor, and the reaction was carried out under anaerobic conditions for 90 minutes. Sampling was carried out every 15 minutes. At the end of the reaction, the collected samples were centrifuged to obtain the supernatant, which was detected by gas chromatograph (Agilent GC8860).
[0084] Comparative Example 4 (without light)
[0085] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0086] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 0.27:100), and transfer to a three-necked flask after complete dissolution. Pass nitrogen for 25 minutes to exclude air. Heat in a 70°C water bath for 4 hours, wash the resulting precipitate several times with deionized water and anhydrous ethanol by centrifugation, and dry at 60°C under vacuum for 12 hours to obtain 0.1% Cu / ZnIn2S4 photocatalyst powder.
[0087] The experiment of decomposing decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction vessel, and the reflux temperature control technology was used to keep the reaction system at a certain temperature. The above-synthesized 0.1% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, the solvent (N,N-dimethylformamide), etc. were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was carried out every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, and the supernatant was detected by gas chromatograph (Agilent GC8860).
[0088] Comparative Example 5 (Methanol as Solvent)
[0089] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0090] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 0.27:100), and transfer to a three-necked flask after complete dissolution. Pass nitrogen for 25 minutes to exclude air. Heat in a 70°C water bath for 4 hours, wash the resulting precipitate several times with deionized water and anhydrous ethanol by centrifugation, and dry at 60°C under vacuum for 12 hours to obtain 0.1% Cu / ZnIn2S4 photocatalyst powder.
[0091] The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction container. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain temperature; the above-synthesized 0.1% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, and the solvent (methanol) were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was performed every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, which was detected by a gas chromatograph (Agilent GC8860).
[0092] Comparative Example 6 (isopropanol as solvent)
[0093] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0094] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 0.27:100), and transfer to a three-necked flask after complete dissolution. Pass nitrogen for 25 minutes to exclude air. Heat in a 70°C water bath for 4 hours, wash the resulting precipitate several times with deionized water and anhydrous ethanol by centrifugation, and dry at 60°C under vacuum for 12 hours to obtain 0.1% Cu / ZnIn2S4 photocatalyst powder.
[0095] The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction container. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain temperature; the above-synthesized 0.1% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, and the solvent (N,N-dimethylformamide) were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was performed every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, which was detected by a gas chromatograph (Agilent GC8860).
[0096] Comparative Example 7 (acetonitrile as solvent)
[0097] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0098] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 0.27:100), and transfer to a three-necked flask after complete dissolution. Pass nitrogen for 25 minutes to exclude air. Heat in a 70°C water bath for 4 hours, wash the resulting precipitate several times with deionized water and anhydrous ethanol by centrifugation, and dry at 60°C under vacuum for 12 hours to obtain 0.1% Cu / ZnIn2S4 photocatalyst powder.
[0099] The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction container. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain temperature; the above-synthesized 0.1% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, and the solvent (N,N-dimethylformamide) were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was performed every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, which was detected by a gas chromatograph (Agilent GC8860).
[0100] Comparative Example 8 (N,N-dimethylacetamide as solvent)
[0101] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0102] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of copper chloride dihydrate (10 g / L) (copper chloride dihydrate and indium zinc sulfide are added at a mass ratio of 0.27:100), and transfer to a three-necked flask after complete dissolution. Pass nitrogen for 25 minutes to exclude air. Heat in a 70°C water bath for 4 hours, wash the resulting precipitate several times with deionized water and anhydrous ethanol by centrifugation, and dry at 60°C under vacuum for 12 hours to obtain 0.1% Cu / ZnIn2S4 photocatalyst powder.
[0103] The experiment of photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction container. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain temperature; the above-synthesized 0.1% Cu / ZnIn2S4, the target pollutant decachlorobiphenyl, and the solvent (N,N-dimethylacetamide) were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was performed every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, which was detected by a gas chromatograph (Agilent GC8860).
[0104] Comparative Example 9 (0.1% Au / ZnIn2S4)
[0105] 0.2876 g of zinc sulfate heptahydrate and 0.5865 g of indium trichloride tetrahydrate were dissolved in a mixed solution of 15 ml of water and 15 ml of ethanol, stirred for 30 minutes, and then 0.605 g of thioacetamide was added and stirred for 30 minutes. The above solution was transferred to a 50 ml autoclave, heat treated in an oven at 180°C for 12 hours, and then cooled to room temperature; the obtained precipitate was washed with deionized water and anhydrous ethanol for multiple times, and dried at 60°C under vacuum conditions for 12 hours to obtain indium zinc sulfide powder.
[0106] Add 200 mg of indium zinc sulfide powder to 150 ml of deionized water and stir for 10 minutes to evenly disperse the indium zinc sulfide. Add a certain amount of hydrated chloroauric acid (10 g / L) (gold content and indium zinc sulfide are added at a mass ratio of 0.1:100), and transfer to a three-necked flask after complete dissolution. Pass nitrogen for 25 minutes to exclude air. Heat in a 70°C water bath for 4 hours, wash the resulting precipitate with deionized water and anhydrous ethanol by centrifugation several times, and dry under vacuum conditions at 60°C for 12 hours to obtain 0.1% Au / ZnIn2S4 photocatalyst powder.
[0107] The comparative sample was tested and found to have Au nanoclusters of about 1 nanometer deposited on the catalyst powder. The photocatalytic degradation of decachlorobiphenyl was carried out in a glass-enclosed heat-resistant reaction vessel. A 300-watt xenon lamp was used as a visible light source; a reflux temperature control technology was used to keep the reaction system at a certain temperature; the above-synthesized 0.1% Au / ZnIn2S4, the target pollutant decachlorobiphenyl, and the solvent (N,N-dimethylformamide) were added to the reactor, and the reaction was carried out for 90 minutes under anaerobic conditions. Sampling was performed every 15 minutes. At the end of the reaction, each sample was centrifuged to obtain the supernatant, which was tested using a gas chromatograph (Agilent GC8860).
[0108] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0109] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A catalyst for reducing decachlorobiphenyl, comprising Flower-ball-shaped indium zinc sulfide as a carrier; And the copper nano clusters loaded on the carrier, the loading mass of which is 0.01-0.25% of the mass of indium zinc sulfide, and the size of the copper nano clusters is 0.5-2 nanometers.
2. The catalyst for reducing decachlorobiphenyl according to claim 1, characterized in that: The carrier has a nanosheet structure, and there are gaps between the nanosheets. The copper nanoclusters are at least formed in the nanosheets or in the gaps between the nanosheets.
3. A method for preparing a catalyst for reducing decachlorobiphenyl according to any one of claims 1 to 2, comprising: Dispersing a zinc salt, an indium salt and a sulfur source in a mixed solvent including water and a dispersant, performing a solvent thermal reaction under heating to obtain a reaction product, and centrifuging, washing and separating the product to obtain a flower ball-shaped indium zinc sulfide carrier; The indium zinc sulfide carrier is dispersed in deionized water to form a suspension, and then copper salt is added. After uniform dispersion, an inert gas is introduced to remove oxygen, and the product is heated, centrifuged, washed, and dried.
4. The method for preparing a catalyst for reducing decachlorobiphenyl according to claim 3, characterized in that: The zinc salt and indium salt are both water-soluble salts.
5. The method for preparing a catalyst for reducing decachlorobiphenyl according to claim 3, characterized in that: The volume ratio of water to dispersant is 1:(0.1-10).
6. The method for preparing a catalyst for reducing decachlorobiphenyl according to claim 3, characterized in that: The temperature of the thermal reaction is 160-200°C.
7. The method for preparing a catalyst for reducing decachlorobiphenyl according to claim 3, characterized in that: The heating temperature is 60-100°C.
8. The method for preparing a catalyst for reducing decachlorobiphenyl according to claim 3, characterized in that: The dispersant is selected from ethanol and glycerol.
9. Use of the catalyst for reduction of decachlorobiphenyl according to any one of claims 1-2 in environmental management.